Effects of Guanxinshutong Capsules as Complementary Treatment in Patients With Chronic Heart Failure: Study Protocol for a Randomized Controlled Trial - Wang, Yu; Xu, Jiaping; Yang, Jiehong; Zhang, Ling; Pan, Yuanjiang; Dou, Liping; Zhou, Peng; Xu, Yizhou; Li, Chang; He, Yu; Zhou, Huifen; Yu, Li; et al. (Frontiers in Pharmacology, 2021)
Chronic Heart failure (CHF) is a common cardiovascular disease with high mortality and poor prognosis, which bring heavy burdens to society and family. Traditional Chinese medicine (TCM) has been extensively used as a complementary treatment for CHF. Guanxinshutong capsules (GXST), is commonly used for the treatment of coronary heart disease (CHD) currently. Both experimental research and small-sample clinical trials have shown that GXST could attenuate CHF. However, the effects of GXST as a complementary medicine in the treatment of CHF are lack of high-quality clinical evidence. This is a multi-center, randomized, double-blind, placebo-controlled clinical trial, which aims to further explore the efficacy and safety when using GXST compared with placebo for CHF with reduced left ventricular ejection fraction (LVEF) patients. A total of 480 participants will be randomly assigned to the GXST and placebo group in ratio 2:1. GXST and placebo will be added to the routine treatment for 12 weeks, then followed-up for another 40 weeks. The primary outcome is the 6 min walk distance, and the secondary outcomes include plasma NT-proB-type Natriuretic Peptide levels, New York Heart Association classification, Minnesota Living with Heart Failure Questionnaire scores, echocardiographic parameters, and clinical endpoint events. Adverse events will be monitored throughout the trial. Data will be analyzed in accordance with a predefined statistical analysis plan. This study will provide specifically used of GXST in CHF patients with reduced LVEF.